NATURAL FIBER REINFORCEMENT AND ITS IMPLICATIONS FOR THE COLOR CHANGE OF HEAT-POLYMERIZED ACRYLIC RESIN DENTURE BASES - Endang Prawesthi; Marzia M. Tetelepta; Heldayani (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Acrylic resin, commonly used as a denture base material, has the disadvantage of being prone to fracture during use. Therefore, reinforcement with natural fibers such as ramie and banana stem fibers is required to improve its mechanical strength. However, potential color changes resulting from fiber addition must be considered, as they may affect the aesthetic quality of the denture. Purpose: This study aims to assess the effect of adding natural fibers at different concentrations as reinforcement for acrylic dentures based on discoloration. Method: A total of 42 acrylic resin samples were prepared in accordance with ISO 20795-1:2013 standards. The samples were divided into seven groups: control, addition of ramie fibers 0.5%, 1.5%, 2.5%, and banana stem fibers 0.5%, 1.5%, 2.5%. The natural fibers underwent alkalization using 5% NaOH. Color change was evaluated using the CIELab system with a VITA shade guide. Color change value formula [(ΔL*)2+(Δa*)2+(Δb*)2]½. Data were analyzed using Two-Way ANOVA (p-value < 0.05). Result: The highest mean ΔE value was observed in the group with 2.5% banana stem fiber addition, while the control group had the lowest value. Increasing fiber concentration resulted in greater color change. Both fiber type and fiber concentration significantly influenced color change values. Additionally, a significant interaction between fiber type and concentration was observed. Conclusion: The color change value in the ramie fiber 0.5% group was still considered stable and did not affect aesthetics because ΔE value was below the standard value (3.7). Higher fiber concentrations resulted in greater color changes. The type and concentration of fiber influence the color change.